Living beside a hospital: Attitude of local residents staying in close proximity to hospitals - Ng, Zhen Yu (2022)
The primary objective of this research is to understand and assess the attitude of locals towards semi-obnoxious facilities that brings benefits and risks to locals simultaneously. Hence, this research identified the determinant factors influencing the attitude of locals on the siting of hospitals within residential neighbourhoods and identified the relationship between these factors and local attitude using the Social Cognitive Theory. The theory provides that human’s behaviours are highly influenced by our presence of mind and anticipations or expectations of future occurrences. In order to achieve the objectives of this research, this research has been designed as a quantitative study, in which COVID-19 perceptions, outcome expectations, selfefficacy, social influence and social environment were identified as the factors influencing local attitude. Sample data were collected through a questionnaire that was distributed to Malaysians living near hospitals. In order to perform a thorough analysis of the collected data, the Partial Least Squares – Structural Equation Modelling (PLSSEM) approach was implemented. Additionally, validity and reliability analysis procedures have also been performed including composite reliability, convergent validity and discriminant validity measures. Outer loadings, indicator reliability and Average Variance Extracted (AVE) were involved in examining convergent validity whereas the Heterotrait-monotrait (HTMT) ratio of correlations were applied for the discriminant validity analysis. Nonetheless, the path coefficient (T-values) and Coefficient of Determination (R2 value) were also identified to assess the structural model results. In a nutshell, significant relationships between outcome expectations, self-efficacy as well as social influence and local attitude were observed. Procedural justice, as an element of social environment was also found to be positively related to local attitude. On the other hand, COVID-19 perceptions along with social trust and distributive justice, both as elements under social environment only portrayed insignificant relationships with local attitude.